Effect Incorporated of Oat and Corn Cob Powder on Physicochemical and Sensory Properties of Putu Piring - Fisal Ahmad; Nur Ezzliana Ismail; Tuan Zainazor Tuan Chilek; Amir Izzwan Zamri; Mohamad Khairi Mohd Zainol; Rahijan Abdul Wahab; Mansoor Abdul Hamid (Universitas Negeri Malang, 2021)
The growing consumer demand for healthy food products has turned the interest of industry and researcher in the development of foods enriched with fibre source. Oat and corn cob powder is one of the fibre sources that rich in insoluble fibers, such as cellulose, hemicellulose and lignin which beneficial the consumer in many ways for a healthy diet. The objective of this study was to investigate the effect of oat and corn cob powder incorporation on the sensory acceptability and physicochemical properties of putu piring at different levels of percentage ratio of oat and corn cob (control 0 percent OP: 0 percent CCP A, 0 percent OP: 100 percent CCP B, 30 percent OP:70 percent CCP C, 50 percent OP:50 percent CCP D, 70 percent OP:30 percent CCP E and 100 percent OP: 0 percent CCP F). Physical analysis showed that the colour of putu piring for L* value ranges from 74.17 to 19.76, a* value ranges from 0.23 to 1.90 and b* value ranges from 13.97 to 20.65. Sensory evaluation results showed that putu piring control (formulation A) scored the highest and no significant different (p lower than 0.05) compare followed by 30 percent OP: 70 percent CCP (formulation C) and 50 percent OP: 50 percent CCP (formulation D) in all attributes being evaluated. Proximate analysis showed that putu piring incorporated with oat and corn cob powder has significantly different (p lower than 0.05) in terms of crude fibre content. It is interesting to note that the incorporation of oat and corn cob powder yielded putu piring can improves the nutritive value of the product to become high fibre products.